Dampak Pemberitaan Fajar Cirebon Dalam Pendidikan Politik Tinjauan Undang-Undang Nomor 40 Tahun 1999 Tentang Pers - Hafizd, Jefik; Abdul Hakim, Fadlih; Rana, Mohamad (Equality : Jurnal Hukum dan Keadilan, 2024)
Facing the 2024 general election, there is a need for political education to provide enlightenment to the public in order to provide rational choices for candidates competing in the 2024 election so as to produce competent leaders. One of those involved in providing political outreach through the contribution of the mass media. However, in reality what is happening in society is that people are still consumed by hoax news and also fall prey to dirty election practices. This research aims to examine the impact of reporting from the Fajar Cirebon Newspaper on political education in the 2024 Election in Cirebon City and examine the impact of Law Number 40 of 1999 concerning the Press on mass media reporting in providing political educational information. This research uses empirical juridical methods through a case study research approach. Data collected through interviews, observation, documentation was then analyzed using descriptive analysis methods. It can be seen from the results of this study that the impact of Fajar Cirebon's reporting on political education in the 2024 elections in Cirebon City is that it can have an impact as a shaper of public opinion by providing a forum for judicial candidates or legislative candidates to express their ideas through various platforms available at Fajar Cirebon. Apart from that, the mass media has an impact as a balancer and observer of elections. Then, regarding the impact of the Press Law on mass media reporting in providing political educational information, it can provide benefits felt by the public, such as easy access to political information and a guaranteed level of accuracy, mass media can be present to provide references to circulating issues. And related to producing information, mass media will be more flexible because freedom is guaranteed by the state.